Jag Var värd 50 Lamm - Sarvestani, Nima (Sweden, 2010)
The film follows a 16-year-old Sabere who was only seven when her father died in war. Following a long-practiced tradition in Afghanistan, she was sold three years later to Golmohammad, a member of the Taliban. During the six years, Sabere was both slave and wife, even becoming pregnant four times with miscarriage each time. She eventually escaped and after much effort, made her way to a women's shelter. "I Was Worth 50 Sheep" is the tale of struggle for human dignity and freedom in a war-torn country caught between ancient traditions and a modern world.
Verzio Film Festival Submission
Keywords: Documentary films